Distinctive oil shale pyrolysis behavior in indirectly heated fixed bed with internals. Issue 35 (18th April 2017) - Lin, Lanxin; Lai, Dengguo; Shi, Zhen; Han, Zhennan; Xu, Guangwen
Abstract : Variation of chemical species from pyrolysis with temperature, with light oil/diesel and VGO dominant at temperatures below 450 °C and above 300 °C. Abstract : Intrinsic characteristics of oil shale pyrolysis in a fixed bed reactor with internals have been investigated in this study. Mounting particularly designed internals in fixed bed reactor improved shale oil production to up to 90% yield by Fischer assay. Comparing particle characteristics at different radial positions of the reactors with and without internals demonstrated that, inside the particle bed with internals, the product flow was regulated to move from the high-temperature zone (outer) to low-temperature zone (center), which reduced the secondary reactions of released volatiles. Terminating oil shale pyrolysis at central particle bed temperatures of 150, 300, 450, and 550 °C showed that the contents of vacuum gas oil and heavy oil in the shale oil produced had increased from 9.63 wt% to 53.29 wt%. The volatile contents of particles in the inner layer of the reactor slightly increased in the early stage of pyrolysis and, in turn, decomposed to form pyrolysis products as the temperature was raised. The adsorption or condensation of liquids on the surface of particles gradually increased from the outer region to the central region of the reactor due to the regulated product flow direction and low temperatures in the central zone of the reactor causing heavy components to condense. Increasing the degree of pyrolysis was also found to decrease the alkene, aromatic, and cycloalkane contents in shale oil, but increased those of alkane and heteroatomic compounds. These results demonstrate that adopting internals into oil shale pyrolysis optimized the product flow direction and selectively directed secondary reactions to occur for heavy volatile species only.